2017
DOI: 10.1161/str.48.suppl_1.tp152
|View full text |Cite
|
Sign up to set email alerts
|

Abstract TP152: Correlation of NIH Stroke Scale and Fugl-Meyer Motor Scales in a Longitudinal Stroke Recovery Study: Implication for Feasibility Survey for Stroke Rehabilitation Trial

Abstract: Introduction: Recruitments of stroke recovery trials have been challenging. NIH stroke scale (NIHSS) has been universally collected in the acute stroke phase, but stroke recovery trials generally use Fugl-Meyer Motor Scale (FMMS) for outcome measure as well as patient selection criteria. The knowledge gap on the relationship between the two scales potentially jeopardize the accuracy of clinical trial recruitment feasibility survey that is based on NIHSS in the acute phase. We aimed to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Our analysis performed in a population of patients with AIS of intermediate severity (b-NIHSS [8][9][10][11][12][13][14] shows that long-term functional outcome is specifically associated with the level of their baseline limb motor score of the NI-HSS (b-NIHSS-LMS), in addition to their level of b-NI-HSS. Nested logistic regression analysis showed that b-NI-HSS and b-NIHSS-LMS were independently associated with functional independence (mRS 0-1).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Our analysis performed in a population of patients with AIS of intermediate severity (b-NIHSS [8][9][10][11][12][13][14] shows that long-term functional outcome is specifically associated with the level of their baseline limb motor score of the NI-HSS (b-NIHSS-LMS), in addition to their level of b-NI-HSS. Nested logistic regression analysis showed that b-NI-HSS and b-NIHSS-LMS were independently associated with functional independence (mRS 0-1).…”
Section: Discussionmentioning
confidence: 86%
“…Data from a large clinical trial, the CHInese Medicine Neuroaid Efficacy on Stroke recovery (CHIMES) and its extension (CHIMES-E) study, was used for this analysis [8, 9]. CHIMES is an international, multicentre, randomised, double-blind study comparing a 3-month course of MLC601 (NeuroAiD TM ) to placebo on poststroke recovery assessed with mRS at month 3 and up to month 24 [9, 10].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations